Religiosity, Ease of Use, and Income Drive ZIS Payment Interest - Kaban, Fadhila Putri; Anggraini, Tuti; Tambunan, Khairina (Academia Open, 2025)
General Background: The advancement of digital technology has transformed how religious obligations such as Zakat, Infaq, and Sadaqah (ZIS) are fulfilled, offering more accessible and efficient payment methods. Specific Background: Bank Syariah Indonesia (BSI) provides digital features aimed at facilitating ZIS payments, particularly in urban areas like Medan. Knowledge Gap: Despite the growing use of digital financial services, limited research has explored the factors influencing public preferences in using digital platforms for ZIS payments. Aims: This study aims to examine how income, religiosity, and perceived ease of use affect public interest in using BSI's digital features for ZIS contributions. Results: Employing a quantitative survey method with 97 respondents determined using the Lemeshow algorithm, the findings reveal that income, religiosity, and ease of use significantly influence public interest and intention to pay ZIS via BSI’s digital features. Novelty: This study highlights the integrated role of socio-economic and technological factors in shaping digital religious giving behavior, particularly in a developing urban context. Implications: The results suggest that BSI should enhance its ZIS payment services by improving user interface design and promoting digital convenience, while future studies are encouraged to explore additional influencing variables to enrich this emerging research domain. Highlights: Digital ease boosts ZIS payment engagement. Income, religiosity, and usability are key drivers. BSI's platform needs user-focused improvements. Keywords: Zakat, Infaq, Sadaqah, Digital Banking, User Behavior